Supply chain management: survey in the Brazilian pharmaceutical industry - Machado, Ricardo (Brazilian Journal of Operations & Production Management, 2014)
This research analyses the supply chain management performance of the pharmaceutical industry in Brazil, from the SCOR (Supply Chain Operations Reference) Model point of view, taking five business processes in consideration: planning, supplying, producing and distributing. A survey was conducted in ten pharmaceutical companies located in Goiás, in the country Centre. The results indicates competition takes place between companies and not between supply chains, very little integration occurs between their links (partners), but wrapped in operational information such as quantity and time, than in relation to strategic issues such as planning along the chain. The industries have a great concern about the quality of their products, because this is an essential aspect of competition in the sector. They are far more shrouded with issues of internal improvements than improving the performance of the supply chain as a whole.